Phytoseiidae (Acari: Mesostigmata) of Morocco: new records, descriptions of five new species, re-descriptions of two species, and key for identification - Tixier, Marie-Stephane; Allam, Latifa; Douin, Martial; Kreiter, Serge (Zootaxa, 2016)
The family Phytoseiidae includes more than 2,300 species distributed all over the world. However despite the huge numbers of faunistic surveys carried out for more than 60 years, the fauna of some countries and particular ecosystems remain little explored. This paper reports results of surveys carried out in various regions of Morocco (from Sahara to Atlantic and Mediteranean coasts) in 2002 and 2003. A total of 43 species was found. Among them 19 are new for the Moroccan fauna and five are new to science. This paper provides the descriptions of these five new species, Neoseiulus thymeleae, Transeius audeae, Typhlodromus (Typhlodromus) ballotae, T. (T.) leclanti, T. (T.) mazarii, and re-descriptions of two species (Typhlodromus (T.) setubali and Typhlodromus (Anthoseius) clairathiasae. A key to females of the 52 species now known from Morocco is given.